Studies of breeding habitats and seasonal occurrence of mosquitoes in Putrajaya and Kuala Selangor, with laboratory experiments of guppies and dragonfly nymphs as potential biocontrol predators against mosquito larvae / Siti Nurhafizah Saleeza Ramlee - Ramlee, Siti Nurhafizah Saleeza (2015)
Mosquito control is essential for the control of vector borne diseases. Many synthetic insecticides are widely used for controlling adult and larval mosquito populations. However, there are multirole effects: e.g. the harmful effects of chemicals on non-target organisms, the development of resistance to these chemicals in mosquitoes and the recent resurgence of different mosquito-borne diseases. The objectives of this study are to determine the potential breeding habitats of the mosquitoes, mosquito indices, mosquito species, density of mosquito larvae, perceptions of respondents on bio control and to conduct captivity studies on predator–prey relationships. Entomological surveillance was carried out in six localities in the urban and suburban areas from January until December 2010 to identify potential breeding sites for mosquitoes and mosquito species populations. A total of 442 representative households in six localities were selected. Breeding habitats were sampled outdoors in the surroundings of the housing areas. There was a significant difference in the number of mosquito larvae collected, where the urban areas had a higher density in contrast to suburban areas. The study indicated that the most predominant species found in both areas was Aedes albopictus with gardening utensils as a preferred breeding habitat for urban area and artificial containers for suburban area. Entomological indices were calculated to predict future outbreaks in the localities. Ovitrap surveillance was carried out in one year to study the relationship between ovitrap surveillance and environmental parameters, which revealed no significant difference in the population numbers for both areas and no correlation to the environmental factors. Questionnaires on the perceptions of chemical in mosquito control and the potential use of bio control were distributed to staffs in health office and also public in both study areas. In general the public had high uncertainties (scoring on ‘not sure’ for all the 4 questions given ranging from 47.9% to 27%. This is due to the public being unfamiliar to bio control as indicated in question 1 (56%) in contrast to staff very aware on bio control (75%). Fatigue was the iv most frequently reported symptom by staff and breathing difficulty reported by public. Natural bio control agent surveillance was conducted in both study areas. Poecilicia reticulata and Odonata nymph species was the most natural predator collected at study areas. Three species of Odonata nymphs consumed more Aedes species than Culex species but there was no significant difference in the predator feeding efficiency. In terms of prey preferences of guppy, both male and female consumed more Aedes species than Culex species. The behaviour of mosquito larvae species and predator (guppy and Odonata nymph) species showed direct influence on the predatory activities. All predators exhibited diurnal activities; they were day-time stalkers and actively consumed more mosquito larvae during the day time. The efficiency of predatory activities depends on several factors such as water volume, number of predator, and number of prey density. These results concluded that both common biocontrol agent (guppies) and potential biocontrol agent (Odonata nymphs) are efficient predators in laboratory experiment and thus likely candidates to be utilized as an environmental friendly mosquito management strategy.